'Biospace': The visual rhetoric of space in micrographs. (1st October 2018) - Liljefors, Max
Microscopy can depict small biological entities that are invisible to the naked eye – cells, neurons, chromosomes, molecules, etc. Microbiology thereby grants us visual access to dimensions of our bodily interior that are otherwise imperceptible to us. Often, in micrographs, this infinitesimal inner realm is made to resemble the way cosmic space is represented in astronomical pictures – an 'aesthetic leap' that ties the microcosm of the body to the macrocosm of the universe. This article explores how aesthetic conventions in microbiological images create meaning that transcends their empirical content, and examines the historical precedents of these conventions in the history of anatomy and their contemporary cultural implications.